On the Contrary - McCarthy, Mary (New York : Farrar Straus and Cudahy, 1961)
Mary McCarthy, one of our most brilliant and beloved authors, serves up wit, insight, and her unique worldview in this diverse collection of essays In provocatively titled pieces such as?The Contagion of Ideas,??Tyranny of the Orgasm,? and?No News, or, What Killed the Dog,? Mary McCarthy expresses her frank, unflinching, often contrarian point of view. Nothing--and no one--is safe from her merciless writer's etc...
Keywords: y